Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1161/01.cir.0000160923.04524.5b
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Ambulatory and Home Blood Pressures Compared With Office Blood Pressure in the General Population

Abstract: Background-Studies in hypertensive patients suggest that ambulatory blood pressure (BP) is prognostically superior to office BP. Much less information is available in the general population, however. Obtaining this information was the purpose of the Pressioni Arteriose Monitorate e Loro Associazioni (PAMELA) study. Methods and Results-Office, home, and 24-hour ambulatory BP values were obtained in 2051 subjects between 25 and 74 years of age who were representative of the general population of Monza (Milan, It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
385
1
29

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 895 publications
(429 citation statements)
references
References 47 publications
14
385
1
29
Order By: Relevance
“…15 Given the potential inaccuracies in measurement technique and artificial increases in BP produced by 'white-coat' effects, 2 office or clinic BP measurement could be inferior to ABPM in predicting hypertension-induced organ damage or clinical outcome. [3][4][5][6] In the current study, office BP parameters including SBP, DBP and even PP failed to predict any clinical outcome. On the other hand, ambulatory BP parameters such as 24 h, daytime and nighttime PP predicted not only CVD and mortality but also non-CV and all-cause mortality, suggesting their broad prognostic impacts in hypertensive patients.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…15 Given the potential inaccuracies in measurement technique and artificial increases in BP produced by 'white-coat' effects, 2 office or clinic BP measurement could be inferior to ABPM in predicting hypertension-induced organ damage or clinical outcome. [3][4][5][6] In the current study, office BP parameters including SBP, DBP and even PP failed to predict any clinical outcome. On the other hand, ambulatory BP parameters such as 24 h, daytime and nighttime PP predicted not only CVD and mortality but also non-CV and all-cause mortality, suggesting their broad prognostic impacts in hypertensive patients.…”
Section: Discussioncontrasting
confidence: 49%
“…2 Many studies have confirmed superiority of 24-h ambulatory BP monitoring (ABPM) over office or clinic BP measurement in predicting hypertension-induced organ damage or clinical outcome. [3][4][5][6] To what extent ABPM provides an independent predictive value beyond office BP is of clinical importance, as ABPM is potentially more burdensome and associated with higher costs than office or clinic BP measurements. Previous study mainly focused on ambulatory systolic BP (SBP) 3,4,6,7 or diastolic BP (DBP).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations